Human, Nonhuman, and Chimeric Research: Considering Old Issues with New Research. (9th December 2022) - Sebo, Jeff; Parent, Brendan
Abstract: Human‐nonhuman chimeric research—research on nonhuman animals who contain human cells—is being used to understand human disease and development and to create potential human treatments such as transplantable organs. A proposed advantage of chimeric models is that they can approximate human biology and therefore allow scientists to learn about and improve human health without risking harms to humans. Among the emerging ethical issues being explored is the question of at what point chimeras are "human enough" to have human rights and thus be owed higher standards of research protection than that currently afforded to nonhuman animals. However, this question and other related questions assume that the ethics of experimenting on nonhuman animals have been settled, which they have not. In this essay, we argue that it is imperative to give adequate attention to familiar questions about nonhuman animal research as well as new questions about chimera research and that failure to do so will result in a distorted understanding of the ethics of chimera research .